Mind Matters: Investigating Cognitive impairment Among Sudanese Elderly - Elkhansa Hassabo Mohamed Abdelrahman (Medicine, 2026)
As life expectancy continues to rise, an increasing number of elderly individuals are at heightened risk of cognitive impairment (CI). This is a significant public health concern, as it adversely affects the elderly’s ability to live independently and imposes substantial financial burdens on households and social services. The prevalence of CI doubles every 5 years, impacting 20% of those aged 65 and 45% of those aged 90 and above. This study aimed to assess the prevalence of cognitive impairment among Sudanese elderly and to identify associated factors – particularly age and education – given their established relevance in similar populations. This is an observational descriptive cross-sectional community-based study. The study was conducted in Almaamoura district which is a high socioeconomic area of Khartoum. The study participants were elderly females and males, aged 65 years and above. A total of 143 elderly individuals were chosen using systematic random sampling. Data were collected by door-to-door survey, from October 14, 2021 to November 29, 2021 using an interviewer-administered standardized questionnaire consisting of the Mini-Mental State Examination and a sociodemographic questionnaire. The overall prevalence of cognitive impairment measured among elderly residents of Almaamoura was found to be 12.6%, among them 13 individuals had severe cognitive impairment (9.1%), and 5 individuals had mild CI (3.5%). Both age and education showed significant associations with cognitive impairment. However, only education remained independently associated with CI in the multivariate analysis, with higher education associated with lower odds of CI. This study identified a relatively low prevalence of cognitive impairment among the elderly residents of Almaamoura. This finding may be attributable to the district’s high socioeconomic status and the low proportion of illiterate individuals in the area.